Aaron and Alexander - Brown, Don, 1949- (Roaring Brook Press, 2015)
Aaron Burr and Alexander Hamilton were both fierce patriots during the Revolutionary War, but the politics of the young United States of America put them in constant conflict. Their extraordinary story of bitter fighting and resentment culminates in their famous duel. For young patriots who may not yet know the story, Aaron and Alexander captures the spirit of these two great men who so valiantly served their country and ultimately allowed their pride and ego to cause their demise.